Morphology and Physiochemical Characterization of Perfluorosulfonic Acid (PFSA) Membrane for Electrochemical Application - Mohd Hafiz Md Ali; Mohammad Noor Jalil; Mohamad Nor Amirul Azhar Kamis; Hamizah Mohd Zaki (Journal of Science and Technology, 2025)
This report provides a thorough examination of the surface morphology, chemical content, and physical properties of Perfluorosulfonic Acid (PFSA) membrane which is commonly utilised as a conductive membrane in fuel cells, ionic batteries, and electrolysers. This experimental effort is separated into two parts: morphological characterisation and physicochemical analysis, which aim to improve understanding of the membrane functional qualities. The membrane surface and cross-sectional characteristics were examined at varied magnifications using Field Emission Scanning Electron Microscopy (FESEM) and Energy-Dispersive X-ray Spectroscopy (EDX). The EDX results revealed that the membrane surface is predominantly composed of carbon (C), oxygen (O), manganese (Mn), and nickel (Ni), accounting for 22.82% by mass, whereas the cross-section analysis revealed higher mass percentages of titanium (Ti), sulphur (S), oxygen (O), carbon (C), and fluorine (F), totalling 53.51%. Tensile testing confirmed the membrane’s strength, with a tensile stress of 13.71 N/mm² and an elongation at break of 73.73%. Thermal stability and breakdown behaviour were determined using Thermogravimetric Analysis (TGA), which validated this membrane thermal endurance at 422oC degradation temperatures. These findings provide significant understanding into the surface morphology and structural functional features of PFSA membrane which allow its optimisation for advanced electrochemical applications.